Greening the Existing Building (Chancellery Building - University Technical Malaysia Melaka) - Al-Ani, Mustafa Khudhur (Journal of Mechanical Engineering and Technology (JMET), 2018)
Buildings contribute significantly to the environmental and economic issues, as they consume a high amount of energy and water. As a building consumes energy, it contributes to emissions of carbon dioxide which lead to environmental pollution. These factors have a negative impact on the environment and the economy among other issues. Green building practices and approaches can considerably reduce or eliminate negative ecological and economic impacts. This study aims to “greening the existing building” and achieve the “Certified” rating level according to the GBI classification, taking into consideration estimated cost. The green building audit results show the total current building rating level is only 18 off 100 points based on the major six criteria that shows the existing Chancellery building achieves a low rating level when evaluated according to the GBI rating system. To achieve a “Certified Rating Level” of (50 points) this study proposes improvements of existing building’s criteria (Retrofitting). The economic analysis involves the estimation of costs included in “Greening Existing Building” and the potential savings acquired from “Retrofitting”.